The capital of dreams : a novel - O'Neill, Heather (HarperPerennial, 2024)
"From the hugely acclaimed author beloved by literary lights, including Emily St. John Mandel, Kelly Link, and Mona Awad, a dark dystopian fairytale about an idyllic country ravaged by war-and a girl torn between safety and loyalty. Sofia Bottom lives in Elysia, a small country forgotten by Europe. But inside its borders, the old myths of trees that come alive and faeries who live among their roots have given way to an explosion of the arts and the consolations of philosophy. From the clarinetists to the cabaret singers, no artist is as revered as Sofia's brilliant mother, the writer Clara Bottom. How can fourteen-year-old Sofia, with her tin ear and enduring love of ancient myths, ever hope to win her mother's love? When the country's greatest enemy invades, and the Capital is under threat, Clara turns to her daughter to smuggle her new manuscript to safety on the last train evacuating children from the city. But when the train draws to a suspicious halt in the middle of a forest, Sofia is forced to run for her life and loses her mother's most prized possession. Frightened and alone in a country at war, Sofia must find a way to reclaim what she has lost. On an epic journey through woods and razed towns, colliding with soldiers, survivors, and other lost children, Sofia must make the choice between kindness and her own survival. In this stunning novel set in an imaginative world yet reflective of our own times, Heather O'Neill delivers a vivid, breathtaking dark fairytale of life, death, and betrayal"--